Chapter Il museo dell'educazione: una nuova prospettiva di Public History per la formazione docente - merlo, giordana (Studi e saggi, 2019)
Referring to the pedagogical utopia of the great intrinsic change to a history designed for a large audience, i.e. Public History, this contribution addresses the possibility of rethinking the museum of education as a space of historical-educational knowledge aimed at a composite audience, including the future teachers appointed to train the younger generations.